Diversity Management and Organizational Performance: Mediation and Moderation of Commitment, Person-job fit and Empowerment - Silva, Lindomar Pinto da; Pessina, Maria Elisa Huber; Castro, Miguel Angel Rivera (Review of Business Management, 2024)
Purpose – This article aims to identify the diversity management effect on organizational performance in the Brazilian context. It also aims to assess the role of commitment, and the person-job fit as mediators, as well the empowerment as a moderating variable in the relationship between diversity management and performance. Theoretical framework – We present and discuss the concepts of diversity management, person-job fit, structural empowerment, and commitment and their relationships. Design/methodology/approach – This is a quantitative study using structural equation modeling, mediation and moderation between variables. Data were collected through a questionnaire administered between April and November 2022. The sample obtained was 568 individuals. Findings – Diversity management positively affects organizational performance, and commitment acts as a mediating variable in this relationship. Empowerment positively moderates the relationship between diversity management and performance. It was also found that diversity management positively impacts both commitment and person-job fit. Research Practical & Social implications – Organizations can benefit from greater performance both by increasing diversity management practices and by practices that increase the commitment and empowerment of their workers, since in the presence of a higher level of empowerment the relationship between diversity management and performance is increased. Originality/value – This provides relevant suggestions about the role played by both diversity management and empowerment, which working together can improve the organization’s performance, especially in Brazil where studies of this nature are rare.